Microalgae, sunlight, and starch: low cell concentration is optimal for outdoor production under nutrient stress - A. Six; P. Chambonnière; P. Alvarez; S. Fon-Sing; C. Lancelon-Pin; J.-L. Putaux; J.-F. Sassi; Y. Li-Beisson; G. Fleury (Bioresource Technology, 2026)

Antinociceptive Action of New Water-Soluble Molecule, a Representative of Hexaazaisowurtzitane Class - S. G. Krylova; E. A. Kiseleva; D. A. Kulagina; T. N. Povet’eva; P. V. Kul’pin; V. V. Eremina; N. A. Alekseeva; M. Yu. Minakova; E. P. Zueva; S. V. Sysolyatin; V. V. Zhdanov (Bulletin of Experimental Biology and Medicine, 2025)

Seasonal variation of the chemical content and source identification of PM2.5 in a mixed landuse in Iran - M. Zare Shahne; N. R. Haghighat; V. Hosseini; G. Uzu; A. Taheri; S. Darfeuil; P. Ginot; J.-L. Besombes; M. Pin; J.-L. Jaffrezo; A. Shamloo (International Journal of Environmental Science and Technology, 2025)

Involvement of Receptor Apparatus in the Realization of Antinociceptive Activity of Songorine - Yu. V. Nesterova; A. V. Mukhomedzyanov; T. N. Povetyeva; N. I. Suslov; P. V. Kul’pin; O. G. Afanas’eva; A. V. Vychuzhanina; O. Yu. Rybalkina; G. N. Zyuz’kov; V. V. Zhdanov; M. Yu. Minakova (Bulletin of Experimental Biology and Medicine, 2025)

From raw microalgae to bioplastics: Conversion of Chlorella vulgaris starch granules into thermoplastic starch - A. Six; D. Dauvillée; C. Lancelon-Pin; A. Dimitriades-Lemaire; A. Compadre; C. Dubreuil; P. Alvarez; J.-F. Sassi; Y. Li-Beisson; J.-L. Putaux; N. Le Moigne; G. Fleury (Carbohydrate Polymers, 2024)

Comparative Study of the Anxiolytic Activity of Songorine in Elevated Plus Maze Test and by Recording Ultrasonic Vocalizations - Yu. V. Nesterova; O. V. Vsyakikh; P. V. Kul’pin; T. N. Povetyeva; G. N. Zyuz’kov; N. I. Suslov; V. V. Zhdanov; E. A. Losev (Bulletin of Experimental Biology and Medicine, 2024)

Red light induces starch accumulation in Chlorella vulgaris without affecting photosynthesis efficiency, unlike abiotic stress - A. Six; A. Dimitriades-Lemaire; C. Lancelon-Pin; J.-L. Putaux; D. Dauvillée; D. Petroutsos; P. Alvarez Diaz; J.-F. Sassi; Y. Li-Beisson; G. Fleury (Algal Research, 2024)

Geochronological record of Cadomian exterior orogen reworking in bi-modal igneous protoliths of the Cabo Ortegal Allochthon (NW Iberia): the Cambrian onset of the Palaeozoic plate-tectonic cycle - A. Beranoaguirre; B. Ábalos; S. García de Madinabeitia; J-L. Paquette; C. Pin; M.E. Sánchez Lorda; J.F. Santos Zalduegui; P. Puelles; J.I. Gil Ibarguchi (International Geology Review, 2024)

Genomic prediction of agronomic and malting quality traits in six-rowed winter barley - G. Charmet; P. A. Pin; M. Schmitt; N. Leroy; B. Claustres; C. Burt; A. Genty (Euphytica, 2023)
While two-rowed barley is usually preferred for malting and beer-making, six-rowed malting barley varieties appeared in Europe around 30 years ago, and several breeders have dedicated improvement programs on this specific germplasm. In this study, we evaluated the feasibility of genomic prediction for yield and malting related traits using 679 breeding lines from two French barley breeders, as well as a set of recently registered varieties. These lines were evaluated in five locations and two harvest years in an unbalanced design. Although the germplasm from the two breeders does show some trend towards differentiation, globally the whole panel did not show a clear-cut genetic structure. Predictive ability of GBLUP was evaluated through random cross-validation within and across breeder sets, and using cross-prediction between breeder sets. Results show moderate to high predictive ability (PA), particularly for malt friability and β-glucan content, for which predictive ability of 0.8 was obtained with training populations as small as 105 registered varieties and across breeding sets. The long range of useful linkage disequilibrium in this particular germplasm allows using as few as 2000 to 5000 markers to obtain high PA. Other prediction methods such as Bayesian LASSO, Bayes Cpi or EGBLUP did not improve predictive ability. These results are very encouraging for implementing genomic prediction of malting quality traits in applied breeding programs.

Antinociceptive Effect of Ethowurtzine, a New Compound from the Class of Hexaazaizowurzitane - S. G. Krylova; E. A. Kiseleva; T. N. Povet’eva; Yu. V. Nesterova; O. Yu. Rybalkina; P. V. Kul’pin; O. G. Afanas’eva; D. A. Kulagina; V. V. Eremina; O. V. Baibakova; E. P. Zueva; N. I. Suslov; et al. (Bulletin of Experimental Biology and Medicine, 2022)

Association between household cleaning product profiles evaluated by the Ménag’Score® index and asthma symptoms among women from the SEPAGES cohort - Pierre Lemire; Emmanuel Chevallier; Sarah Lyon-Caen; Etienne Sévin; Anne Boudier; Emilie Pacheco Da Silva; Christian De Thuin; Rémy Slama; Orianne Dumas; Valérie Siroux; Nicole Le Moual; E. Eyriey; et al. (International Archives of Occupational and Environmental Health, 2022)

Some Aspects of Investigation of the Central Mechanism of Antinociceptive Effect of a New Analgetic from the Hexaazaisowurtzitane Group - S. G. Krylova; K. A. Lopatina; Yu. V. Nesterova; T. N. Povet’eva; P. V. Kul’pin; O. G. Afanas’eva; D. A. Kulagina; E. A. Safonova; E. P. Zueva; N. I. Suslov; S. V. Sysolyatin (Bulletin of Experimental Biology and Medicine, 2021)

Effect of Lithium Preparations on Cerebral Electrophysiological Activity in Rats - V. I. Konenkov; L. N. Rachkovskaya; A. Yu. Letyagin; N. I. Suslov; A. V. Shurlygina; M. V. Robinson; M. A. Korolev; A. A. Kotlyarova; T. V. Popova; E. E. Rachkovskii; T. N. Povet’eva; N. V. Shilova; et al. (Bulletin of Experimental Biology and Medicine, 2018)

Psychopharmacological Effects of JNK Inhibitor in Posthypoxic Encephalopathy and Mechanisms of Their Development - G. N. Zyuz’kov; N. I. Suslov; T. N. Povet’eva; Yu. V. Nesterova; O. G. Afanas’eva; E. V. Udut; L. A. Miroshnichenko; E. V. Simanina; T. Yu. Polyakova; L. A. Stavrova; A. V. Chaikovskii; P. V. Kul’pin; et al. (Bulletin of Experimental Biology and Medicine, 2017)

Early Cambrian granitoids of North Gondwana margin in the transition from a convergent setting to intra-continental rifting (Ossa-Morena Zone, SW Iberia) - T. Sánchez-García; M. F. Pereira; F. Bellido; M. Chichorro; J. B. Silva; P. Valverde-Vaquero; Ch. Pin; A. R. Solá (International Journal of Earth Sciences, 2014)

Typhoon Disturbance and Forest Dynamics: Lessons from a Northwest Pacific Subtropical Forest - Teng-Chiu Lin; Steven P. Hamburg; Kuo-Chuan Lin; Lih-Jih Wang; Chung-Te Chang; Yue-Joe Hsia; Matthew A. Vadeboncoeur; Cathy M. Mabry McMullen; Chiung-Pin Liu (Ecosystems, 2011)

Detection of a novel border disease virus subgroup in Tunisian sheep - F. Thabti; C. Letellier; S. Hammami; M. Ppin; M. Ribire; A. Mesplde; P. Kerkhofs; P. Russo (Archives of Virology, 2005)

The Activation Mechanism of Class-III G-Protein Coupled Receptors - J.-P. Pin; J. Kniazeff; C. Goudet; A.-S. Bessis; P. Rondard; J. Liu; F. Acher; T. Galvez; L. Przeau (Medicinal Chemistry Research, 2004)